Legal Protection for Whistleblowers of Corruption Crime Bring to Fairness - Irwan Effendi (Sociological Jurisprudence Journal, 2024)
The legal protection provided to the whistleblower is still ineffective and far from feeling safe and perfect and in the event that the complainant of a crime still often gets criminalized and discriminated against, the legal protection provided is still not sufficient to fulfill the sense of justice of what the complainant has given. This research uses normative legal research. The formulation of the problem in this study (1) Does the concept of legal protection for whistleblowers as contained in Law Number 13 of 2006 concerning amendments to Law Number 31 of 2014 regarding sex workers fulfill a sense of justice? and (2) What is the expected strategy in order to strengthen the regulation of legal protection for reporters of criminal acts of corruption in a just manner?. The conclusion of this study when viewed from the theory put forward by Lawrence M. Friedman which states that the success or failure of law enforcement is closely related to the legal system. firstly, at the level of substance, the existing regulations are still not sufficient so that more specific rules are needed to regulate legal protection for whistleblowers, the structure whose implementation is still in contact with authorities with other law enforcement officers, the culture of fulfilling the rights of those who report corruption crimes that are In practice, there is still an assessment and fulfillment of rights for reporting corruption crimes and the first strategy is providing education, information about legal protection by law enforcement officers to be given to the public in order to create legal awareness from the community.